Entrepreneurial and attitudinal determinants for adoption of Climate-smart Agriculture technologies in Uganda - Kirungi, D.; Senyange, B.; Wesana, J.; Sseguya, H.; Gellynck, X.; Steur, H. de (Informa UK Limited, 2023)
Climate-Smart Agriculture (CSA) technologies have great potential to minimize climate risks, sequester carbon, improve food security, and achievement of Sustainable Intensification (SI) goals. This makes their adoption a necessity for achieving sustainable agricultural systems. Despite the benefits and all efforts, smallholder farmers in developing countries still have low adoption of CSA technologies. This study explored the determinants of intentions to start and continue adopting CSA technologies. A cross-sectional survey based on the Theories of Planned Behaviour (TPB), Diffusion Of Innovations (DOI), and Entrepreneurial Orientation (EO) was administered to 230 randomly selected smallholder coffee farmers in the Luweero district, Uganda. A Multi-group Structural Equation Model (Multi-group SEM) analysis reveals that more factors determine the intention to start adopting CSA than for intention to continue implementing CSA and the same factors could influence the former and the latter differently. Key recommendations to enhance the uptake and continued adoption of CSA technologies include focusing on raising awareness about the characteristics of CSA technologies, employing a multi-stakeholder approach to remove obstacles that hinder CSA adoption and providing business and entrepreneurial skills training for farmers. Our study findings and recommendations will help different stakeholders in designing more suitable and sustainable CSA technology adoption interventions.